China's Second Continent : How a Million Migrants Are Building a New Empire in Africa - French, Howard W. (New York Vintage Books, 2015)
Discusses China's growing presence in Africa that includes Chinese migrant workers, and economic efforts to improve African infrastructure.
Include Maps and Index
Keywords: China -- Sub-Saharan Africa -- Chinese -- Emigration and immigration -- Immigrants -- Political science